Cloud-Native Mobile Application Development for Optimization and Inventory Management - Tati, Sunun; Muangwai, Alongkorn; Khanongnuch, Thanida; Thampitak, Wichit; Sajjaanggoon, Akachai (Journal of Applied Statistics and Information Technology, 2022)
Nowadays, Supply Chain Management is driven by information instead of human experience or forecasting. Big data helps the business owner to know the quantity of demand which leads to production planning both in terms of quality and quantity. Due to the changing demand customers, it is quite difficult for prediction to specify the amount of demand to the production plan. The researcher then developed a cloud-native mobile application for inventory tracking to store real-time data in the database and pilot it to Sri Kaew Lomkao Company Limited as a case study. The result has shown that the developed application can reduce labor costs by 98.34% and reduce working time by 98.33%.